2009
DOI: 10.1186/1743-7075-6-26
|View full text |Cite
|
Sign up to set email alerts
|

Leucine modulation of mitochondrial mass and oxygen consumption in skeletal muscle cells and adipocytes

Abstract: Background: The effects of dairy on energy metabolism appear to be mediated, in part, by leucine and calcium which regulate both adipocyte and skeletal muscle energy metabolism. We recently demonstrated that leucine and calcitriol regulate fatty acid oxidation in skeletal muscle cells in vitro, with leucine promoting and calcitriol suppressing fatty acid oxidation. Moreover, leucine coordinately regulated adipocyte lipid metabolism to promote flux of lipid to skeletal muscle and regulate metabolic flexibility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 49 publications
5
136
0
1
Order By: Relevance
“…Leucine has previously been shown to increase muscle protein synthesis through stimulation of mammalian target of rapamycin (mTOR) and Akt phosphorylation [1][2][3][4][5]. Despite this anabolic function, leucine has also been shown to promote several processes involved in catabolic metabolism including increased expression of fatty acid oxidation genes [6][7][8][9], heightened oxygen consumption [10,11], and increased mitochondrial content in both skeletal muscle and adipocytes [8,9,11,12]. Biochemical investigations have repeatedly demonstrated that leucine stimulates peroxisome proliferator-activated receptor γ coactivator 1 alpha (PGC-1α) expression leading to increased mitochondrial biosynthesis and heightened metabolic rate [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leucine has previously been shown to increase muscle protein synthesis through stimulation of mammalian target of rapamycin (mTOR) and Akt phosphorylation [1][2][3][4][5]. Despite this anabolic function, leucine has also been shown to promote several processes involved in catabolic metabolism including increased expression of fatty acid oxidation genes [6][7][8][9], heightened oxygen consumption [10,11], and increased mitochondrial content in both skeletal muscle and adipocytes [8,9,11,12]. Biochemical investigations have repeatedly demonstrated that leucine stimulates peroxisome proliferator-activated receptor γ coactivator 1 alpha (PGC-1α) expression leading to increased mitochondrial biosynthesis and heightened metabolic rate [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this anabolic function, leucine has also been shown to promote several processes involved in catabolic metabolism including increased expression of fatty acid oxidation genes [6][7][8][9], heightened oxygen consumption [10,11], and increased mitochondrial content in both skeletal muscle and adipocytes [8,9,11,12]. Biochemical investigations have repeatedly demonstrated that leucine stimulates peroxisome proliferator-activated receptor γ coactivator 1 alpha (PGC-1α) expression leading to increased mitochondrial biosynthesis and heightened metabolic rate [11][12][13][14]. While the ability of leucine to stimulate PGC-1α expression has been reproducible, the mechanism(s) through which leucine acts to increase mitochondrial content and PGC-1α activation have not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…20 The mechanisms underlying these observations remain obscure, although activation of key regulators of mitochondrial biogenesis and fat oxidation such as SIRT1, PGC1α, and/or AMPK may be particularly sensitive to exercise and timely PS, particularly in response to the amino acid leucine. 1,20,[44][45][46] These effects could increase mitochondrial mass and fat oxidation capacity, 20,46 although additional studies will be needed to reveal the mechanism underlying increased fat oxidation and its sensitivity to timely PS. Equally unexplained was the lack of improvement for fat oxidation in the dPS group, although we have previously reported that gains in aerobic capacity were lower in the dPS than iPS conditioning group.…”
Section: Discussionmentioning
confidence: 99%
“…As a functional amino acid ), Leu is a key element that can increase mitochondrial biogenesis and fatty acid oxidation in muscle cells. Leu (0.5 mM) can promote mitochondrial biogenesis in both C2C12 myocytes and 3T3-L1 adipocytes, and modulates skeletal muscle energy metabolism by regulating peroxisome proliferator-activated receptor gamma coactivator 1α and SIRT-1 expression levels (Sun and Zemel 2009). C2C12 myotubes were treated with physiologically relevant concentrations of Leu, α-KIC, or HMB to investigate the direct role of Leu versus its metabolites in mitochondrial biogenesis and fatty acid oxidation (Stancliffe 2012).…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
“…In those tissues, Leu promotes protein synthesis via activating the mammalian target of rapamycin (mTOR) signaling pathway, and also enhances energy homeostasis through augmenting mitochondrial biogenesis and fatty acid oxidation (Filhiol 2012). Moreover, Leu provides skeletal muscles with an increased flux of lipids, supplying energy substrates to support protein synthesis (Sun and Zemel 2009). However, when skeletal muscle is exposed to physiological concentrations of fatty acids in vivo, oxidation of leucine as a significant source of ATP is likely limited (Jobgen et al 2006;Wu et al 2014) primarily because the activity of branched-chain α-keto acid dehydrogenase activity (BCKD) is relatively low in this tissue (Wu and Thompson 1987).…”
Section: Introductionmentioning
confidence: 99%